2003
DOI: 10.1002/chem.200204704
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Two Isomeric closo‐[(η5‐C5H5)FePC2B8H10] Phosphadicarbaborane Analogues of Ferrocene via Isolable η1‐Bonded Complexes of the [7‐{(η5‐C5H5)Fe(CO)2}‐(η1nido‐PC2B8H10)] Type

Abstract: The reaction of nido-[7,8,9-PC(2)B(8)H(11)] (1) with [[CpFe(CO)(2)](2)] (Cp=eta(5)-C(5)H(5) (-)) in benzene (reflux, 3 days) gave an eta(1)-bonded complex [7-Fp-(eta(1)-nido-7,8,9,-PC(2)B(8)H(10))] (2; Fp=CpFe(CO)(2); yield 38 %). A similar reaction at elevated temperatures (xylene, reflux 24 h) gave the isomeric complex [7-Fp-(eta(1)-nido-7,9,10-PC(2)B(8)H(10))] (3; yield 28 %) together with the fully sandwiched complexes [1-Cp-closo-1,2,4,5-FePC(2)B(8)H(10)] 4 a (yield 30%) and [1-Cp-closo-1,2,4,8-FePC(2)B(8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Melting points were measured in sealed capillaries under argon and are uncorrected. Multinuclear ( 1 H, 11 B, and 13 C) NMR spectroscopy was performed essentially with the instrumentation described in other related papers from our laboratories 15. The 11 B and 13 C chemical shifts are given in the following manner: δ(exp.…”
Section: Methodsmentioning
confidence: 99%
“…Melting points were measured in sealed capillaries under argon and are uncorrected. Multinuclear ( 1 H, 11 B, and 13 C) NMR spectroscopy was performed essentially with the instrumentation described in other related papers from our laboratories 15. The 11 B and 13 C chemical shifts are given in the following manner: δ(exp.…”
Section: Methodsmentioning
confidence: 99%
“…The distances from the metal centre Fe1 to the cluster heteroatoms C5, P2 and P3, at 2.053(6), 2.2616(17) and 2.2633(16) A ˚, respectively, approximate to similar separations found crystallographically for the isostructural complex [1-Cpcloso-1,2,4,5-FePC 2 B 8 H 10 ] (6). 1 The intracluster C-B, P-B, and B-B distances are also in similar ranges to those of 6. The structure determination also confirms the symmetrical arrangement of the iron, carbon and phosphorus heteroatoms within the twelve-vertex closo cage.…”
Section: Structural Studiesmentioning
confidence: 66%
“…There is current interest in the synthesis and chemistry of closo twelve-vertex ferraphosphacarborane compounds because of their high stabilities and their structural analogies to ferrocene. In this area we have recently reported 1 that the reaction between neutral nido-7,8,9-PC 2 B 8 H 11 2 and [CpFe(CO) 2 ] 2 yields closo complexes [1-Cp-1,2,4,5-FePC 2 B 8 H 10 ] and [1-Cp-1,2,4,8-FePC 2 B 8 H 10 ]. We have also demonstrated that these compounds can form via the isolatable g 1bonded nido intermediates [7-{CpFe(CO) 2 }-7,8,9,-PC 2 B 8 H 10 ] and [7-{CpFe(CO) 2 }-7,9,10-PC 2 B 8 H 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other chemicals were reagent or analytical grade and were used as purchased. The analytical TLC and column chromatography, melting points, mass spectrometry, and NMR spectroscopy were essentially carried out as described in other work from our laboratories 12…”
Section: Methodsmentioning
confidence: 99%